KEBIJAKAN PEMERINTAH KOTA PEKANBARU TERHADAP PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA TAHUN 2011-2012 - PUTRA, TENGKU NARA PRIMA; ", ISRIL (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study wants to determine and analyze Government Policy PekanbaruCity Empowerment Of Organization and Traders of Five Feet Period 2011-2012.The background of this study is not the implementation of a well GovernmentPolicy Pekanbaru City Empowerment Of Organization and Traders of Five FeetYear 2011-2012 sourced from the rampant activity hawkers and inconsistencies inthe implementation of Government Regulation of the Minister of Home AffairsNumber 20 Year 2012 and Regional Regulation Pekanbaru No. 11 Year 2001.Another problem is the high level of urbanization and yet optimal controlGovernment Pekanbaru City the supervision of Street Vendors. This study aims todetermine Implementation analyze Government Policy Pekanbaru CityEmpowerment Of Organization and Traders of Five Feet Period 2011-2012 and tofind out what are the factors that affect the implementation of this policy, basedon the theory of public policy and public policy implementation. This study usedqualitative methods implemented in the city of Pekanbaru, the data obtained eitherdirectly or indirectly, which is then analyzed using descriptive data analysistechniques.Based on the review and analysis of data showed ImplementationGovernment Policy Pekanbaru City Empowerment Of Organization and Tradersyear 2011-2012 not going well. It was marked from the increasing number ofstreet vendors are popping up in almost every sub-district in the city of Pekanbaruand a lack of public understanding of the Regional Regulation No. 11 Year 2001Pekanbaru About Planning and Empowerment of Street Vendors in the city ofPekanbaru which in practice often lead to conflict between the Government andtraders as well as the difficulty of Pekanbaru city government to do thearrangement and empowerment. The factors that affect the implementation of theRegional Regulation No. 11 Year 2001 Pekanbaru About Planning andEmpowerment of Street Vendors is the lack of supervision, high urbanization andbureaucratic structures that are less responsive.Keyword; Policies, Regulations Regional Pekanbaru City, Planning andEmpowerment hawkers pavement.